Efeito do bandeamento e taxa de resfriamento na ocorrência de austenita retida em aço baixo carbono com adições de manganês e silício - Helder Carvalho Ferreira (2015)
This work presents the research of cooling rate effect and the presence of banding in occurrence of retained austenite (RA) in low-carbon steel with addition of manganese and silicon, used for the manufacture of MIG electrode, ER70S-6 class. X-ray diffraction was used to quantify low level of RA (volume fraction below 6 %), presented as block/film or martensite-austenite constituent (MA). It was performed decomposition of K1 and K2 wavelengths through optimization of Pearson VII. Jominy tests were also used to evaluate the influence of cooling rate on occurrence of RA. Samples were collected at several distances from the water cooled end. The evaluation of occurrence of banding on RA was carried out by comparing as-rolled samples with samples treated at high temperature and long length of time. As a result, it was possible to combine the effects of cooling rate and structure in the occurrence of RA in the studied steel. It was observed that RA increases with the cooling rate, reaches a peak and stabilizes at high rates. For the as-rolled sample, i.e. with banded structure, the peak of RA is found close to the cooling rate of 16.7 °C/s, and for homogenized material, this peak occurs at a lower rate, approximately 10 °C/s. For banded and homogenized structures, the total elimination of the occurrence of this phase occurred at cooling rates of 0.83 and 0.17 °C/s, respectively. Similar behavior was seen regarding the variation of carbon content in RA at cooling rate. For both structures, the occurrences of RA maxima volume fraction coincide with maxima in the carbon content of the austenite. In the evaluation of the wire rod passed through Stelmor® cooling process, it was observed that the greatest concentration of RA is in the regions of greater mass concentration. These positions correspond, in the tensile test, to the highest strength levels and smallest values of necking. By adding titanium to the steel composition, it was possible to reduce significantly the volume fraction of RA in the asrolled wire rod, and to reach satisfactory levels of resistance and necking, thereby allowing direct drawing from the 5.50 mm to 1.88 mm wire gauge.